Initial Diagnosis and Detection of Very Late Local Recurrence of a Ductal Prostate Cancer due to a Ureteral Stone - Manolis Pratsinis; Charlotte Düwel; Olivia Köhle; Annette Enzler-Tschudy; Hans-Peter Schmid; Patrick Betschart (Case Reports in Urology)
We report the case of a 74-year-old patient in whom a ductal prostate cancer was incidentally endoscopically diagnosed in the course of ureteral stenting due to a left distal ureteral stone. The initial PSA was 0.8 μg/l and the digital rectal examination was not suspicious. A radical prostatectomy was performed, and the ensuing follow-up was unremarkable with no signs of recurrence. Fourteen years later, the patient presented with an obstructive pyelonephritis due to a left-sided ureteral stone requiring ureteral stenting. An exophytic tumor was seen in the lining of vesicourethral anastomosis and surgically excised after the pyelonephritis subsided. The histopathological and immunohistochemical analysis revealed a ductal cancer of the prostate consistent with a late local recurrence. Serum PSA was below the limit of detection. Re-staging performed by an MRI of the pelvis, thoracoabdominal CT scan, and gallium-68 PSMA-PET did not reveal any other signs of disease. The ensuing follow-up is planned with regular flexible cystoscopy and computed thoracoabdominopelvic CT scans.